Micro-sized nano-porous Si/C anodes for lithium ion batteries. (January 2015) - Tian, Huajun; Tan, Xiaojian; Xin, Fengxia; Wang, Chunsheng; Han, Weiqiang
Abstract: The unique micro-sized (2–10 µm) Si/C composites consisting of 20 nm carbon coated secondary Si were synthesized from the abundant and low cost Al–Si alloy ingot by acid etching, ball-milling and carbonization procedure. The nano-porous Si/C composites provide a capacity of 1182 mAh g −1 at a current density of 50 mAg −1, 952 mAh g −1 at 200 mAg −1, 815 mAh g −1 at 500 mAg −1, and maintain 86.8% of initial capacity after 300 cycles. Even at a much higher current density of 10 A/g, the porous Si/C anode can still provide capacities of >200 mAh g −1 . Its superior rate capability and cycling stability of micro-sized nano-porous Si/C anodes is because it takes advantage of both long cycle life of nano-Si and high volumetric/gravimetric capacity of micro-Si. The hierarchical porous micro-scale Si/C with the carbon coating can stabilize the SEI layer and the inside pore provides adequate space for Si expansion, relaxing the stress/strain. The hierarchical Si/C with exceptional electrochemical performance is prepared by a simple, low-cost and saleable synthesis method, making it very promising for a large-scale production of high-performance Si-based anode materials in high-energy lithium-ion batteries. Graphical abstract: Highlights: Hierarchical micro-sized Si/C composites consisting of 20 nm carbon coated secondary Si were synthesized from the abundant and low cost Al–Si alloy ingot. Micro-sized Si/C anodes consisting of carbon coated nano-scale porous Si units took advantage of both long cycle life of nano-Si and high volumetric/gravimetric capacity of micro-Si. The hierarchical Si/C with exceptional electrochemical performance was prepared by a simple, low-cost and saleable synthesis method, making it very promising for a large-scale production of high-performance Si-based anode materials in high-energy lithium-ion batteries.